Smart Agronomy of Wheat Cultivation in Riverbed of Betawa through Natural And Organic Farming under Changing Climate (Global Journal of Science Frontier Research, 2022)
The present innovative and introductive experiment was laid out during two consecutive rabi seasons of 2009-10 and 2010-11 under "Farmers Participatory Action Research Project on Water/Water Harvesting" (Scheme funded by Central Water Commission, New Delhi). Since, the extensive farming almost closed up because all cultivable land saturated under cultivation of crops and other agricultural enterprises. During the visit of Bundelk hand region of U.P. for scheme work, the riverbed open after water receding of Betawa river was seen. The open riverbed was found suitable for cultivation of winter season crops. Riverbed was suffered from the nodulation of rocks (Maurang), but siltation was fertile. Therefore, the site was selected for cultivation of wheat because it has better nutrients status. The riverbed soil was fertilized with organic manure i.e., FYM @ 200 q/ha, vermi cost + vermi-eggs@10 q/ha and mustard cake @ 5 q/ha for major and minor plant nutrients and loosened the riverbed soil. Wheat cv. WH-147 was planted on 15 November and harvested 20 March after 125 days of planting in both experimental seasons.
Keywords: betawa river; 2018; gada2019; rich siltation; river bed soil; water receding; WH-147